TGF-β1 Improves Biomechanical Strength by Extracellular Matrix Accumulation Without Increasing the Number of Tenogenic Lineage Cells in a Rat Rotator Cuff Repair Model. (August 2017) - Arimura, Hitoshi; Shukunami, Chisa; Tokunaga, Takuya; Karasugi, Tatsuki; Okamoto, Nobukazu; Taniwaki, Takuya; Sakamoto, Hidetoshi; Mizuta, Hiroshi; Hiraki, Yuji
Background: Transforming growth factor β1 (TGF-β1) positively regulates the tenogenic marker genes scleraxis ( Scx ) and tenomodulin ( Tnmd ) in mesenchymal progenitors in vitro. However, little is known about the effect of TGF-β1 on the expression of tenogenic markers during rotator cuff (RC) healing in rats. Hypothesis: TGF-β1 improves the biomechanical properties and histological maturity of reparative tissue in a rat RC repair model by stimulating the growth of tenogenic cells. Study Design: Controlled laboratory study. Methods: Adult male Sprague-Dawley rats (N = 180) underwent unilateral supraspinatus tendon-to-bone surgical repair and were randomly treated with a gelatin hydrogel presoaked in TGF-β1 (100 ng) or phosphate-buffered saline. The effects of TGF-β1 on RC healing were investigated at 2, 4, 6, 8, and 12 weeks postoperatively by immunostaining for proliferating cell nuclear antigen, by real-time reverse transcription polymerase chain reaction and in situ hybridization or immunostaining for enthesis-related markers (SRY-box containing gene 9 [ Sox9 ], Scx, and Tnmd ), and by real-time reverse transcription polymerase chain reaction and immunostaining for type I and III collagen. At 6 and 12 weeks postoperatively, biomechanical testing, micro–computed tomography, and biochemical analysis were also performed. At 2 and 4 weeks postoperatively, mesenchymal stem cell–related markers, phospho-Smad2, and matrix metalloproteinase 9 (MMP-9) and MMP-13 were assessed by immunostaining. Results: The TGF-β1-treated group had significantly higher ultimate load to failure and tissue volume at 6 and 12 weeks postoperatively and a higher collagen content at 12 weeks compared with the saline group. Tendon-related gene expression, histological maturity, cell proliferation, and mesenchymal stem cell–related marker immunoreactivity were not affected by exogenously administrated TGF-β1 at all time points. In the TGF-β1-treated group, the percentage of phospho-Smad2-positive cells within the healing tissue increased, whereas the expression of MMP-9 and MMP-13 significantly decreased at 2 and 4 weeks postoperatively. Conclusion: TGF-β1 enhances formation of tough fibrous tissues at the healing site by inhibiting MMP-9 and MMP-13 expression to increase collagen accumulation but without the growth of tenogenic lineage cells. Clinical Relevance: These findings suggest that TGF-β1 could be used for enhancing biomechanical strength after RC surgical repair.